Konstruksi Gender dalam Film Kucumbu Tubuh Indahku - Vigor M. Loematta; Rini Rinawati (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The film Kucumbu Body Indahku tells the life journey of a Lengger dancer named Juno in interpreting her body and gender philosophy. From the time Juno was interested in this type of art, he was educated at a dance studio near his home, when he was left by his father to work. Juno did not study for a long time at the studio, because his teacher was arrested as a result of a murder committed. After that, Juno stayed with his aunt, where he went back to school, while attending school Juno still deepened his dancing ability by attending extracurricular activities. His school period did not go well when Juno's teacher was arrested by residents for allegedly harassing Juno. The story continued until Juno grew up and worked as a tailor's assistant, where he put his heart to a male boxer who was his customer, until Juno was forced to have same-sex sex with a prospective regional head. From the background of the character, the researcher felt interested to raise the title of this film as a study by taking the gender construction of the film's character as a focus, besides that this film when it was released in the community experienced a number of controversial remarks. Many regions rejected this film because it was allegedly containing elements of Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ) in it. However, despite the accusations directed, this film received a good reception from the film community by winning several awards, and then entered the Academy Awards or Oscar nominations. This research uses a qualitative approach. The method used for analysis and interpretation is Roland Barthes's semiotics, where the codes are divided into three categories of analysis, namely connotation, denotation, and mythology. Then, to dissect the existing gender construction the researcher uses the queer theory as a reference, from the theory the researcher concludes three indicators of gender construction, namely body expression, the identity shown and sexual attraction. Abstrak. Film Kucumbu Tubuh Indahku menceritakan perjalanan hidup penari Lengger bernama Juno dalam memaknai tubuh dan gender. Sedari kecil Juno telah tertarik dengan kesenian ini, ia belajar di sanggar tari dekat rumahnya, ketika ia ditinggal oleh ayahnya untuk bekerja. Masa sekolahnya tidak berjalan baik ketika guru Juno ditangkap warga, diduga melakukan pelecehan terhadap Juno. Cerita terus berlanjut hingga Juno dipaksa berhubungan seksual dengan calon kepala daerah pria. Banyak daerah yang menolak penayangan karena disinyalir mengandung unsur Lesbian, Gay, Bisexual, Transgender, dan Queer . Tetapi, dibalik tuduhan itu, film ini mendapat sambutan baik dari insan perfilman dengan dimenangkannya beberapa pengharggan hingga masuk nominasi Academy Awards. Penelitian ini menggunakan pendekatan kualitatif. Metode yang digunakan untuk analisis dan interpretasi, semiotika Roland Barthes, di mana kode-kode yang ada dibagi menjadi tiga yaitu konotasi, denotasi, dan mitos. Untuk membedah konstruksi gender yang ada digunakan teori queer sebagai acuan, dari teori tersebut tersimpulkan tiga indikator konstruksi gender, yaitu ekspresi tubuh, identitas yang ditunjukkan dan ketertarikan seksual.